Profitabilitas, Struktur Aktiva, Likuiditas, dan Ukuran Perusahaan terhadap Struktur Modal pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2016-2019 - Yosia Ananda Putra Sibagariang; Jessy Safitri Sitorus (IPM2KPE, 2022)
This study aims to determine the effect of profitability, asset structure, liquidity, and company size on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange in 2016-2019. This research method is descriptive quantitative. The sample is 48 food and beverage companies listed on the IDX in 2016-2019. Data were analyzed by multiple linear regression. The results showed, a) the profitability variable (X1) had a t-count value of 3.887 with a t-tabulation price of 2.016; b) the asset structure variable (X2) has a t count of -1.353 < t table of 2.016. with a significant level of 0.183 > 0.05; c) the variable liquidity (X3) has a t-value of -1.911 < t-tabulation of 2.016 with a relevant level of 0.063>0.05; d) company size variable (X4) has a t value of 1.270 < t table of 2.016 with a significant level of 0.211 > 0.05. In conclusion, profitability individually has a positive and significant effect on capital structure, while individual asset structure has a negative and significant effect on capital structure, liquidity individually has a negative and significant effect on capital structure, and firm size does not have a positive and significant effect on capital structure. Keywords: Liquidity, Profitability, Asset Structure, Capital Structure, Company Size